STRATEGI MANAJEMEN PENDIDIKAN ISLAM DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM TINGKAT DASAR PADA KONTEKS KARAKTER AKHLAKUL KARIMAH - Erlin Ermawati; Sudadi; Bahrani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the strategic planning of Islamic education management, describe its implementation in shaping students' akhlakul karimah character, and identify its supporting and inhibiting factors at the primary education level in Muhammadiyah Elementary School. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation study. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, while data validity was ensured through source and method triangulation. The findings reveal three main conclusions: first, strategic planning is carried out participatively and adaptively with Islamic values as the philosophical foundation of all educational programs; second, strategy implementation is conducted through teacher role modeling (uswah hasanah), structured daily habituation, and character value integration in formal learning supported by akhlakul karimah-oriented academic supervision; third, implementation success is sustained by leadership commitment, teacher professionalism, and parental involvement, while negative external environmental influences and inconsistent family support remain the primary inhibiting factors. This study contributes to the development of a holistic and integrative Islamic education management model oriented toward nurturing a generation of Muslims with noble character in the contemporary era